Daya Dukung Kawasan Wisata Pantai di Pantai Pandawa Kecamatan Kuta Selatan, Kabupaten Badung, Bali - Eka Putri, I Dewa Ayu Ratna Raksa; Astawa Karang, I Wayan Gede; Ria Puspitha, Ni Luh Putu (Journal of Marine Research and Technology, 2020)
Pandawa Beach is a famous tourist destination among locals and foreigners,  located in  Kutuh village, Kuta Selatan sub district, Badung regency, Bali. Tourism activities can create various negative impacts on the surrounding environment because increased human interference in ecologically areas, the massive development of tourism has affected balance of nature ecosystem in an area, especially the carrying capacity. Carrying capacity is a concept developed for natural resources and environmental management to prevent the occurrence of environmental disturbance or destruction. The researches about carrying capacity it so necessary to find out, has suitable or non suitable carrying capacity, especially at Pandawa beach on the high season at the beginning year (January-early March 2019). The method used in this research was conducted with field observations for primary data collection with the method of interviews to tourists, while the secondary data was obtained from shore managers and literature studies. The data required was wide of the area, the time required enjoyed based on activities type. The result found that wide of area (Lt) required for tourism in high season was 95.09 , time required for tourist activities (Wp) was 2.08 hours. The carrying capacity of Pandawa beach is 9.907 people/day or 307.111 people/month, 3.685.327 people/year which is classified as under carrying capacity. With a carrying capacity of 9.907 people/day, it would be very good if the utilization of the carrying capacity of only about 5.000 people/ day. When the high season conditions in 2019 the number of tourists visiting Pandawa Beach is still in a reasonable condition or classified as under carrying capacity.